A New Approach of Complier Design in Context of Lexical Analyzer - Gupta, Surbhi; Yadav, Nipun; Dewan, Vikrant (IJRDO -Journal of Computer Science Engineering, 2015)
A compiler translates and/or compiles a program written in a suitable source language into anequivalent target language through a number of stages. Starting with recognition of tokenthrough target code generation provide a basis for communication interface between a user anda processor in significant amount of time. A new approach GLAP model for design and timecomplexity analysis of lexical analyser is proposed in this paper. In the model different stepsof tokenize (generation of tokens) through lexemes, and better input system implementationhave been introduced. Disk access and state machine driven Lex are also reflected in the modeltowards its complete utility. The model also introduces generation of parser. Implementationof symbol table and its interface using stack is another innovation of the model in acceptancewith both theoretically and in implementation widely.